LOSSLESS COMPRESSION OF THE HALFTONE IMAGES BASED ON RUN-LENGTH ENCODING - H. K. Al-Bahadily; E. G. Makeichik; V. Yu. Tsviatkou; V. K. Kanapelka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The modified algorithms length coding to compress grayscale images without losses that are different from the basic algorithm taking into account the likelihood of the occurrence of pixel values and images that reduce the size of the encoded data.